Expenditure patterns of young single adults: two recent generations compared. - Paulin, Geoffrey (Monthly Labor Review, 2008)
The article examines the expenditure and income patterns for single, never-married young adults in the U.S. It highlights differences in the spending patterns for young, never-married adults in 2004-2005 and their counterparts in 1984-1985. It also determines the economic status of the two groups of singles in each period. The data used is the Interview Survey which is a component of the Consumer Expenditure Survey (CE). Accordingly, CE is a detailed source of expenditure information collected directly from households by the federal government.